Association of MCP-1 -2518 A/G Single Nucleotide Polymorphism with the Serum Level of CRP in Slovak Patients with Ischemic Heart Disease, Angina Pectoris, and Hypertension - Maria Bucova; Jan Lietava; Peter Penz; Frantisek Mrazek; Jana Petrkova; Marian Bernadic; Martin Petrek (Hindawi Limited, 2009)
The aim of our work was to find if MCP-1 -2518 (A/G) single nucleotide polymorphism (SNP) influences somehow the serum concentrations of high-sensitive CRP (hsCRP) both in patients suffering from ischemic heart disease (IHD), myocardial infarction (MI), angina pectoris (AP), and hypertension (HT) and in control group of healthy subjects. Totally, 263 patients with the diagnosis of IHD, out of them 89 with MI, 145 with AP, 205 with HT, and also 67 healthy subjects were included in the study. First, we estimated the serum levels of hsCRP. We found that patients with AP had significantly higher serum level of hsCRP than both control group of healthy subjects (P=.043) and IHD patients without AP (P=.026). The presence of the mutant G allele statistically significantly correlated with the higher serum levels of hsCRP in patients with IHD (P=.016), AP (P=.004), and HT (P=.013). Higher correlations were found in men (AP: P=.019; HT: P=.047). In all cases the highest levels of hsCRP were found both in patients and healthy controls with homozygous GG genotype.